FAMILY SUPPORT AS A SUPPORT SYSTEM IN PREVENTING INFECTION AND DISEASE RECURENCE: DUKUNGAN KELUARGA SEBAGAI SUPPORT SYSTEM DALAM PENCEGAHAN INFEKSI DAN KEKAMBUHAN PENYAKIT - Nurlaily, Ari Pebru; Prastiwi, Firman; Murharyati, Atiek; Listrikawati, Martini (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Amilies play a crucial role in preventing the transmission and recurrence of disease by fostering care and instilling habits of clean and healthy living-most notably, the proper practice of handwashing. Although the COVID-19 pandemic has officially ended, new cases continue to emerge, and other infectious diseases remain a public health concern. Therefore, family support is essential to achieving optimal health, in line with the Sustainable Development Goals (SDGs). Objective: To improve the health status of families and communities, and to prevent infections and disease recurrence particularly among mothers in the Mojogedang 1 area. Method: The community service activity included lectures, presentations using banners and canva-based materials about family support and infection prevention. The program was conducted at the Mental Revolution House (WCS), covering the stages from assessment to evaluation. Results: The proportion of participants categorized as having “good” family support increased from 16.8% to 66.7%, while those with “good” knowledge rose from 25% to 91.7%. Conclusion: Empowered family support serves as the most effective system for preventing infectious diseases and their recurrence.